Evaluation of using spot urine to replace 24 h urine sodium and potassium excretions. Issue 11 (9th May 2014) - Hooft van Huysduynen, Eveline JC; Hulshof, Paul JM; van Lee, Linde; Geelen, Anouk; Feskens, Edith JM; van 't Veer, Pieter; van Woerkum, Cees JM; de Vries, Jeanne HM
Abstract: Objective: The most accurate method to estimate Na and K intakes is to determine 24 h urinary excretions of these minerals. However, collecting 24 h urine is burdensome. Therefore it was studied whether spot urine could be used to replace 24 h urine samples. Design: Participants collected 24 h urine and kept one voiding sample separate. Na, K and creatinine concentrations were analysed in both 24 h and spot urine samples. Also 24 h excretions of Na and K were predicted from spot urine concentrations using the Tanaka and Danish methods. Setting: In 2011 and 2012, urine samples were collected and brought to the study centre at Wageningen University, the Netherlands. Subjects: Women ( n 147) aged 19–26 years. Results: According to p -aminobenzoic acid excretions, 127 urine collections were complete. Correlations of Na:creatinine, K:creatinine and Na:K between spot urine and 24 h urine were 0·68, 0·57 and 0·64, respectively. Mean 24 h Na excretion predicted with the Tanaka method was higher (difference 21·2 mmol/d, P <0·001) than the measured excretion of 131·6 mmol/d and mean 24 h Na excretion predicted with the Danish method was similar (difference 3·2 mmol/d, P =0·417) to the measured excretion. The mean 24 h K excretion predicted with the Tanaka method was higher (difference 13·6 mmol/d, P <0·001) than the measured excretion of 66·8 mmol/d. Bland–Altman plots showed large individual differences between predicted and measured 24 h Na and K excretions. Conclusions: The ratios of Na:creatinine and K:creatinine in spot urine were reasonably well associated with their respective ratios in 24 h urine and appear to predict mean 24 h Na excretion of these young, Caucasian women.